2005
DOI: 10.1007/s10194-005-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

A woman with daily headaches

Abstract: Headache, and migraine in particular, is the main neurological reason for consultation. We present the case of a 48–year–old woman who experienced a transformation of her episodic migraine attacks into daily headache episodes due to the ingestion of biscuits containing wheat as their main ingredient. This experience emphasises that a good clinical interview remains the most important point in the diagnosis and management of headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although the mechanisms of IgG-mediated food allergy have not been fully elucidated, increase in the production of IgG antibodies and cytokines 18 via food allergy antigens has been proposed to result in an inflammation response that seems to play an important role in the pathophysiology of migraine attacks. 19 Likewise, offering a potential explanation for how dietary antigens could trigger migraine attacks, IBS patients were shown to have a greater area of intestinal mucosa occupied by mast cells than do healthy control individuals. 20 Additionally, the gut permeability defect identified in IBS patient was shown to lead to increased intake of dietary antigens to lamina propria that may ultimately result in raised IgG antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of IgG-mediated food allergy have not been fully elucidated, increase in the production of IgG antibodies and cytokines 18 via food allergy antigens has been proposed to result in an inflammation response that seems to play an important role in the pathophysiology of migraine attacks. 19 Likewise, offering a potential explanation for how dietary antigens could trigger migraine attacks, IBS patients were shown to have a greater area of intestinal mucosa occupied by mast cells than do healthy control individuals. 20 Additionally, the gut permeability defect identified in IBS patient was shown to lead to increased intake of dietary antigens to lamina propria that may ultimately result in raised IgG antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Pascol J et al [20] have studied a woman with daily headache and found that dietary factors must be specifically examined into migraine patients particularly in those cases with frequent attacks and no evidence of analgesic abuse or psychiatric comorbidity. Merrett J et al [21] have studied food related antibodies in headache patients and reinvestigated the role of IgE mediated food allergy in migraine by using a highly sensitive IgE RAST technique to determine circulating levels of specific IgE to four foods commonly supposed to trigger migraine.…”
Section: Upine Publishersmentioning
confidence: 99%
“…It has been proposed that food-allergy antigens transported by way of mast cells activate T helper and B lymphocytes, increasing the production of IgG antibodies and cytokines (19). Then the increased IgG antibodies and cytokines would lead to an inflammation response, which, as pointed out by Alpay and co-workers (11), seems to play an important role in the pathophysiology of migraine attacks. Supporting this hypothesis, a recent study has shown that anti-food IgG antibodies in obese juveniles are associated with systemic inflammation (20).…”
mentioning
confidence: 90%
“…With all these negative results, there has been almost no interest in studying, clinically or pathophysiologically, the relationship between migraine and diet in the last two decades. As just one significant example, both the aminergic hypothesis and IgE-mediated allergy hypothesis have totally disappeared as potential explanations for the pathophysiology of migraine attacks in the last edition of The Headaches (10), even though we do continue to see many patients who experience migraine attacks when they eat certain foods or whose migraine improves on some diets (11). In this issue of Cephalalgia, Alpay and co-workers report the results of an interesting randomised, double-blind, cross-over, headache diary–based trial with 30 patients having migraine without aura (12).…”
mentioning
confidence: 99%